2020
DOI: 10.1021/acsami.0c10570
|View full text |Cite
|
Sign up to set email alerts
|

Complementary Metal–Oxide–Semiconductor Compatible Deposition of Nanoscale Transition-Metal Nitride Thin Films for Plasmonic Applications

Abstract: Transition-metal nitrides have received significant interest for use within plasmonic and optoelectronic devices because of their tunability and environmental stability. However, the deposition temperature remains a significant barrier to widespread adoption through the integration of transition-metal nitrides as plasmonic materials within complementary metal− oxide−semiconductor (CMOS) fabrication processes. Binary, ternary, and layered plasmonic transition-metal nitride thin films based on titanium and niobi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…Recent studies have also demonstrated the surface plasmon-assisted optical response of the metallic TiN in the visible and infrared spectral ranges. The exceptional combination of thermal and chemical stability, which extends even to temperatures as high as 1400 °C, while concurrently exhibiting plasmonic activity, underscores TiN as an extraordinarily promising candidate for a number of applications, including photothermal-based plasmonic applications, solar absorbers, photothermal medical therapy, , and heat-assisted magnetic recording (HAMR) to name a few . As such, studies have been undertaken to improve the optical properties of TiN to shift plasmonic quality even closer to that of gold. …”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have also demonstrated the surface plasmon-assisted optical response of the metallic TiN in the visible and infrared spectral ranges. The exceptional combination of thermal and chemical stability, which extends even to temperatures as high as 1400 °C, while concurrently exhibiting plasmonic activity, underscores TiN as an extraordinarily promising candidate for a number of applications, including photothermal-based plasmonic applications, solar absorbers, photothermal medical therapy, , and heat-assisted magnetic recording (HAMR) to name a few . As such, studies have been undertaken to improve the optical properties of TiN to shift plasmonic quality even closer to that of gold. …”
Section: Introductionmentioning
confidence: 99%
“…Gold exhibits the formation of acceptor and donor levels inside the intrinsic energy band gap in silicon. The introduction of this substance into the semiconductor material results in its contamination and the subsequent formation of a deep-level trap. ,, To remedy these fundamental issues, titanium nitride (TiN) has gained considerable attention as an alternative plasmonic material, offering advantages such as high-temperature stability, biocompatibility mechanical rigidity, chemical resistance, geopolitical availability, and compatibility with CMOS technology. …”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7] There is a renewed interest in titanium nitride (TiN) as a plasmonic metamaterial 4,[8][9][10][11] as a cathode material for energy storage [12][13][14][15] and catalysis. [16][17][18] The nanomechanical properties, surface defects and stoichiometry are crucial for the overall device functionality and reliability 5,6,[19][20][21][22][23] . Vacuum-based physical vapor deposition (PVD) techniques such as sputtering, 24,25 high-power impulse magnetron sputtering, 20 pulsed laser deposition, 26,27 and cathodic vacuum arc (CVA) deposition 28 have been widely used for synthesizing the TiN thin films.…”
Section: Introductionmentioning
confidence: 99%
“…[16][17][18] The nanomechanical properties, surface defects and stoichiometry are crucial for the overall device functionality and reliability 5,6,[19][20][21][22][23] . Vacuum-based physical vapor deposition (PVD) techniques such as sputtering, 24,25 high-power impulse magnetron sputtering, 20 pulsed laser deposition, 26,27 and cathodic vacuum arc (CVA) deposition 28 have been widely used for synthesizing the TiN thin films. However, measuring the local properties of metal-nitrides is a daunting task as the inert nature of the nitrogen molecules and the undesirable formation of oxides can lead to nanoscopic inhomogeneities in mechanical properties.…”
Section: Introductionmentioning
confidence: 99%